Comparison instead of translation: The bilingual distinctive dictionary of synonyms as a complement to the traditional bilingual dictionary / Vergleich statt Übersetzung: Das bilinguale distinktive Synonymenwörterbuch als Ergänzung zum traditionellen zwei - Farhidnia, Arash (Kalbotyra, 2011)
In the preceding article we showed that the traditional alphabetical bilingual dictionary which tries to assign two vocabularies to each other by atomization of their units is confronted with the serious problem of anisomorphism, i.e. with incongruences between the vocabularies of two languages. This problem shows itself very clear if we carefully observe the way the traditional bilingual dictionary tries to translate L1-synonyms into L2-units. Since there are no exact L2-equivalents for the L1-units the bilingual dictionary is often compelled to offer the same L2-equivalents despite of different L1-units. This method results in the complete leveling of subtle differences in the meaning and use conditions of L1-synonyms simply because there are often no such L2-units which correspond to the L1-units concerning meaning and use condition. In our article we work out the outline of a new type of bilingual dictionary in which the vocabulary units of two languages are no longer translated into each other but which are compared with each other on the basis of groups of synonyms. This method allows the comparison of – ideally – all lexical units two languages provide for the expression of an extralinguistical noeme on the one hand, on the other hand it compels the bilingual lexicographer to offer exact definitions of near-synonymous units in both L1- and L2-language. The bilingual distinctive dictionary of synonyms becomes so a highly useful help for language learners who want to get a deeper insight into the lexical possibilities of the foreign language and who want to articulate their thoughts in a stylistically more precise and accurate way.